The Concept of Womanhood: Revisiting the Precolonial Nigerian Woman - Ekpootu, Mfon U. (Researchparks Publishing, 2023)
Womanhood is a concept that has attracted an intensive scholarly gaze spanning multiple disciplines. The focus here is on womanhood as imagined, and demonstrated in the Nigerian milieu. In different historical epochs from pre-colonial to post–colonial Nigeria, the production of knowledge about women was and continues to be essentialized, contested and negotiated. It is the aim of this paper to show the problematic ‘woman’ in pre-colonial Nigerian society. The dictionary definition of womanhood describes it as “a state or condition of being a woman”. The question this begs is what does it mean to be a woman? Do women have a commonality as observed in the case of people of the same race? Efforts to answer this question throw up the definitional murkiness of the ‘woman space’. The complexity of the category “woman” is seen in the different meanings attached to it historically, from the philosophical constructions of the woman in classical antiquity as an ‘underdeveloped man’; to the Victorian woman as ‘the angel in the house’, the domesticated wife; the colonized woman as hapless victim in need of saving and the postcolonial narrative of womanhood as one of difference in performance. Given that womanhood as a performative act is context specific, this paper revisits the precolonial Nigerian woman, in her complexity and knowledge production. The work adopts intersectionality as its theoretical framework to understand the crisscrossing of social, and political identities, roles and duties of women in pre-colonial Nigeria and how they experienced being a woman from different positions of power and social status. The paper contributes to the literature on African women.